One-dimensional simulation for attemperator based on commissioning data of coal-fired steam power plant. (25th February 2017) - Cho, Baekhyun; Choi, Geunwon; Uruno, Yumi; Kim, Hyunseo; Chung, Jaewon; Kim, Hyojun; Lee, Kihyun
Graphical abstract: Highlights: An attemperator is a device to spray water into the superheated steam. The evaporation was analyzed using the enthalpy balance from the commissioning data. The spray atomization and its concurrent evaporation in an attemperator were physically modeled. A simple one-dimensional simulation was conducted to verify the commissioning results. Abstract: An attemperator is a device that is used to spray water into the superheated steam between the primary, platen, and final superheaters and the reheat lines. The goal of the attemperator is to control the temperature of the superheated steam in accordance with desired turbine-inlet temperature during both steady-state and transient operation. Because the thermowell installed at the attemperator outlet is tied back to the feedback control of the spray water, the spray water should evaporate ahead of the thermowell for accurate control of the steam temperature. In this work, the completion of the evaporation ahead of the thermowell was analyzed using the enthalpy balance from the start-up commissioning data of an 800-MW coal-fired steam power plant. In addition, the phenomena of the spray atomization and its concurrent evaporation in an attemperator were physically modeled, and a simple one-dimensional simulation was conducted to verify the analysis of the commissioning data.